2016
DOI: 10.1111/pedi.12354
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of childhood-onset type 1 diabetes in Biscay, Spain, 1990-2013

Abstract: The IR did not increase in this population during the period studied unlike the results in other Spanish regions and European Countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 28 publications
5
15
1
3
Order By: Relevance
“…For example, data from Sweden collected over 20 years showed a doubling of the incidence from 20 per 100,000 per year to 40 per 100,000 per year, showing a trend similar to that observed in Kuwait. Clearly, our data contribute to the overall conclusion that the global trend of incidence of T1D is still on the rise across the world with a few exceptions such as a recent study from the Biscay region of Spain . Among Kuwaiti children, we found an overall annual increase in T1D incidence of 4.1%, over the last 2 decades.…”
Section: Discussioncontrasting
confidence: 74%
“…For example, data from Sweden collected over 20 years showed a doubling of the incidence from 20 per 100,000 per year to 40 per 100,000 per year, showing a trend similar to that observed in Kuwait. Clearly, our data contribute to the overall conclusion that the global trend of incidence of T1D is still on the rise across the world with a few exceptions such as a recent study from the Biscay region of Spain . Among Kuwaiti children, we found an overall annual increase in T1D incidence of 4.1%, over the last 2 decades.…”
Section: Discussioncontrasting
confidence: 74%
“…In recent years, there has been a debate about whether the incidence of T1D is increasing, decreasing, or has stabilized . On the other hand, some authors believe that the incidence seems to be higher because of an earlier onset .…”
Section: Discussionmentioning
confidence: 99%
“…IAA were determined using a competitive fluid‐phase radioassay which uses [ 125 I]‐labeled recombinant human insulin (Amersham) as antigen and polyethylene glycol for precipitation of immune complexes. GADA (glutamic acid decarboxylase antibodies) and IA2 antibodies were detected using standard radiobinding assay with [ 35 S]‐labeled recombinant human GAD 65 and IA2 antigens obtained by in vitro translation using cDNA clones provided by Dr A. Lernmark (University of Washington, Seattle, WA) and Dr E Bonifacio (Istituto Scientifico San Raffaele, University of Milan, Milan, Italy), respectively …”
Section: Methodsmentioning
confidence: 99%
“…A multitude of studies have revealed a pronounced variation trend of T1D incidence with age. For childhood T1D, incidence increases with age and reaches its peak during the age group 10 to 14 years with only limited inconsistency from studies reporting 5 to 9 years as the fastigium . Conversely, T1D incidence decreases after 14 years of age, and such downward trend persists in adulthood .…”
Section: Epidemiologymentioning
confidence: 99%
“…T1D was initially recognized as a chronic disease among children and young adolescents, but over time, the perspective that T1D can occur at any age has been gradually accepted . The incidence of childhood T1D has been growing globally since the past few decades though stagnation has also been observed in a small number of regions around the world …”
Section: Introductionmentioning
confidence: 99%